Foreign direct investment and regional trade liberalization : a viable answer for economic development? - Lee, Yong-Shik (2005)
Considers whether free trade and FDI may replace the role of the state in facilitating industries for development and promote economic development without initial economic welfare losses associated with state industrial promotion and trade protection. Examines how recent developments in the regulatory environment concerning FTAs and FDI affect the development interest of developing countries.